THE POSSIBILITIES OF CORRECTION PARAMETERS OF ONBOARD INERTIAL NAVIGATION SYSTEMS FOR AIRCRAFT BASED ON GRAVIMETRIC MAPS OF THE EARTH - V. V. Popadiev; A. I. Soroka; A. I. Polubehin; V. Y. Tsygankov; S. G. Braytkrayts; R. N. Akinshin; A. V. Khrushchov (Научный вестник МГТУ ГА, 2016)
The possibilities of correction parameters of onboard inertial navigation systems for aircraft based on gravimetric maps are considered. Data on the vertical component of the gravity force anomaly is averaged over a regular grid; horizontal components of the force are calculated on the basis of map-chart of deflexures of plumb line. We give general information about the Earth's gravitaty field, the study thereof, as well as basic working formulas.